2017
DOI: 10.1002/jor.23707
|View full text |Cite
|
Sign up to set email alerts
|

Key developments that impacted the field of mechanobiology and mechanotransduction

Abstract: Advances in mechanobiology have evolved through insights from multiple disciplines including structural engineering, biomechanics, vascular biology, and orthopaedics. In this paper, we reviewed the impact of key reports related to the study of applied loads on tissues and cells and the resulting signal transduction pathways. We addressed how technology has helped advance the burgeoning field of mechanobiology (over 33,600 publications from 1970 to 2016). We analyzed the impact of critical ideas and then determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 173 publications
0
51
0
1
Order By: Relevance
“…This was summarized in a mathematical expression, where amplitude, frequency, duty cycle (loading duration, duration of resting phase), number of cycles, wall shear stress rate, wall shear stress, and substrate stiffness were discussed as potential critical factors for strain-induced responses on cells. 34 Although in these early observations the number of suggested contributing factors was quite large, we were able to formulate a simpler mathematical expression to describe the cellular response to a relatively wide range of fluid shear stresses, including loading amplitude and duty cycle. When applying the approximate area under the curve for square functions and error functions as a compound factor for loading amplitude and duration to explain the modulation of osteoclast formation, a strong correlation could be seen, suggesting that it is the combination of those two parameters that determine the directionality and strength of the osteoclast-modulating response.…”
Section: Discussionmentioning
confidence: 99%
“…This was summarized in a mathematical expression, where amplitude, frequency, duty cycle (loading duration, duration of resting phase), number of cycles, wall shear stress rate, wall shear stress, and substrate stiffness were discussed as potential critical factors for strain-induced responses on cells. 34 Although in these early observations the number of suggested contributing factors was quite large, we were able to formulate a simpler mathematical expression to describe the cellular response to a relatively wide range of fluid shear stresses, including loading amplitude and duty cycle. When applying the approximate area under the curve for square functions and error functions as a compound factor for loading amplitude and duration to explain the modulation of osteoclast formation, a strong correlation could be seen, suggesting that it is the combination of those two parameters that determine the directionality and strength of the osteoclast-modulating response.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians in the 19th century observed that bones can remodel their structure to support mechanical loads after a fracture (Wolff, 2010a, 2010b, 2011). More recently, Carter and Hayes (1976) continued this work and renewed the focus on mechanobiology of bone (reviewed by Carter, Beaupré, Giori, and Helms (1998) and Wall et al (2017)). The field has since expanded to study other tissues and cell types.…”
Section: Mechanobiologymentioning
confidence: 96%
“…The biological mechanisms underlying mechanotransduction are areas of intense study (Wall et al, 2017). In cells of the osteoblast lineage, early signaling events activated by mechanical stimuli such as fluid flow and membrane stretch include transient elevation in the concentration of cytosolic free calcium ([Ca 2+ ] i ) (Jing et al, 2014;Lorusso et al, 2016;Mikolajewicz, Zimmermann, Willie, & Komarova, 2018;Thi, Suadicani, Schaffler, Weinbaum, & Spray, 2013).…”
mentioning
confidence: 99%